2017
DOI: 10.1002/cncr.30899
|View full text |Cite
|
Sign up to set email alerts
|

Survival among children diagnosed with acute lymphoblastic leukemia in the United States, by race and age, 2001 to 2009: Findings from the CONCORD‐2 study

Abstract: BACKGROUND: Acute lymphoblastic leukemia (ALL) is the most common childhood malignancy. This report describes the survival of children with ALL in the United States using the most comprehensive and up-to-date cancer registry data. METHODS: Data from 37 state cancer registries that cover approximately 80% of the US population were used. Age-standardized survival up to 5 years was estimated for children aged 0–14 years who were diagnosed with ALL during 2 periods (2001–2003 and 2004–2009). RESULTS: In total,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 42 publications
(145 reference statements)
4
47
0
6
Order By: Relevance
“…Geographic differences in cancer incidence have been previously documented in the United States and Europe using population‐based cancer registries . Geographic differences in survival, similar to incidence, might be related to genetic, environmental, economic, or social factors . This study found relative survival differences between non‐Hispanic white and black patients in the South and between non‐Hispanic white patients, Hispanic patients, and other non‐Hispanic patients in the Midwest.…”
Section: Discussionsupporting
confidence: 56%
“…Geographic differences in cancer incidence have been previously documented in the United States and Europe using population‐based cancer registries . Geographic differences in survival, similar to incidence, might be related to genetic, environmental, economic, or social factors . This study found relative survival differences between non‐Hispanic white and black patients in the South and between non‐Hispanic white patients, Hispanic patients, and other non‐Hispanic patients in the Midwest.…”
Section: Discussionsupporting
confidence: 56%
“…We observed that age-standardized 5-year net survival for lung cancer (19.0%) was 4.2% higher than that for liver cancer (14.8%) 18 but lower than for the other cancers addressed in this Supplement, including stomach cancer (29.0%), 19 ovarian cancer (41.0%), 20 cervical cancer (62.8%), 21 rectal cancer (64.0%), 22 colon cancer (64.6%), 23 acute lymphoblastic leukemia in children (88.1%), 24 breast cancer (88.6%), 25 and prostate cancer (96.9%). 26 …”
Section: Discussionmentioning
confidence: 68%
“…If an age‐specific estimate could not be obtained, we merged data for adjacent age groups and assigned the combined estimate to both age groups. If 2 or more age‐specific estimates could not be obtained, we present only the pooled, unstandardized estimates for all ages combined: these estimates are italicized in Supporting Tables 2 and 3 in other articles of this supplement …”
Section: Methodsmentioning
confidence: 99%